Chemotaxonomic Study of Four Subspecies of Pinus nigra Arn. Grown in Common Garden Based on Essential Oil Composition - Sondes Fkiri; Faten Mezni; Ghayth Rigane; Ridha Ben Salem; Hanene Ghazghazi; M. Larbi Khouja; Zouheir Nasr; Abdelhamid Khaldi (Journal of Food Quality)
The aim of this study was to investigate the chemical diversity of Pinus nigra Arn. essential oils. The research was carried out on the needles collected from eighteen provenances of black pine grown in common garden located in West-Northern Tunisia and belonging to four different subspecies (Pinus nigra subsp. nigra, Pinus nigra subsp. salzmannii, Pinus nigra subsp. pallasiana, and Pinus nigra subsp. laricio). Essential oil yields ranged from 0.19% to 0.68%. The obtained essential oils have been analyzed by GC-FID and GC-MS apparatus. Twenty-three constituents accounting about 98% of total essential oil composition were identified. The essential oil compositions appeared to be very different according to their origin. Thus, five main essential oil chemotypes were identified in Pinus nigra plants: caryophyllene oxide, camphene, ß-caryophyllene, α-amorphene, and germacrene D. The chemotaxonomic value of the essential oil compositions was discussed in relation to the results of the multivariate statistical test, including a detailed survey of the available literature data.